A preliminary investigative system to disciplinary inquiries of the Health Professions Council of South Africa, with specific reference to Maxillo-Facial and Oral Surgery - Carstens, Pieter Albert, 1960- (University of Pretoria, 2013)
Thesis (PhD (Dentistry))--University of Pretoria, 2006.